«Nueve ancianos» Anulan la Legislación del New Deal: El Tribunal Supremo Estadounidense y la Ley Agraria1 - Sagredo Santos, Antonia (Revista Complutense de Historia de América, 2006)
When Franklin D. Roosevelt became the president of the United States, the Judicial power was the only one in the Government with a republican majority. Consequently, the New Deal legislative measures found a great deal of opposition within the Judicial branch, where there was a large number of federal district judges who admitted summary proceedings presented by the representatives of different enterprises. The validity of several laws proposed by the Executive and approved by the Legislative, among them the agrarian laws, are questioned in these proceedings. Some of these claims reached the Supreme Court, where conservative judges dominated over the liberals. This fact led to the rejection in this tribunal of the reform proposals promoted by President Roosevelt. One of the laws that the Supreme Court invalidated was the Agricultural Adjustment Act on which the New Deal agrarian reform was based.